From inflammation to pyroptosis: Understanding the consequences of cadmium exposure in chicken liver cells - Lei Li; Hao Xu; Yan Wang; Yu Zhang; Ruiqi Ye; Wen Li; Jingyi Yang; Jiale Wu; Jing Li; Erhui Jin; Mixia Cao; Xiaojin Li; et al. (Ecotoxicology and Environmental Safety, 2024)
Hepatotoxicity is frequently observed following acute cadmium (Cd) exposure in chicken. Oxidative stress and subsequent inflammation are regarded as the main reasons for cadmium-induced liver injury. NOD-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) inflammasome-induced pyroptosis is involved in various inflammatory diseases, including liver injury. Poultry are more susceptible to harmful effects of heavy metals. However, the mechanism of cadmium-induced liver injury in chicken is still elusive. In this study, the effect of cadmium on chicken liver cells and the underlying mechanisms were investigated. The results showed mitochondria was damaged and excessive reactive oxygen species (ROS) were generated in chicken liver cell line LMH after cadmium exposure. Furthermore, cadmium-induced NLRP3 inflammasome activation and the cell membrane rupture indicated LMH cells pyroptosis. The ROS scavengers, acetylcysteine (NAC) and Mito-TEMPO prevented pyroptosis in LMH cells, suggesting that ROS were responsible for the activation of the NLRP3 inflammasome induced by cadmium. Additionally, anti-oxidative transcription factor Nrf2 was inhibited after cadmium exposure, explaining the excessive ROS generation. In summary, our study showed that cadmium leads to ROS generation by inducing mitochondrial damage and inhibiting Nrf2 activity, which promotes NLRP3 inflammasome activation and eventually induces pyroptosis in LMH cells.